Digital Libraries: Social Media and Community Networks 15th International Conference on Asia-Pacific Digital Libraries, ICADL 2013, Bangalore, India, December 9-11, 2013. Proceedings - Urs, Shalini R.; Na, Jin-Cheon.; Buchanan, George; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 15th International Conference on Asia-Pacific Digital Libraries, ICADL 2013, held in Bangalore, India, in December 2013. The 15 revised full papers, 6 revised short papers, and 10 poster papers were carefully reviewed and selected from 87 submissions. The papers are organized in topical sections on information retrieval; social architecture for digital libraries and information policy; digital library applications and systems; data mining for digital libraries; collaboration and communities; analysing social media and social networks; mobile devices and services; and metadata and information extraction.
Information retrieval -- Social architecture for digital libraries and information policy -- Digital library applications and systems -- Data mining for digital libraries -- Collaboration and communities -- Analysing social media and social networks -- Mobile devices and services -- Metadata and information extraction.
Keywords: Computer science; Database management; Information storage and retrieval systems; Text processing (Computer science; Computer Science; Information Storage and Retrieval; Database Management; User Interfaces and Human Computer Interaction; Information Systems Applications (incl. Internet).; Document Preparation and Text Processing